Could Accountant Be Facilitator To Zero Net Emission Programs? - Yanuar Ramadhan; Achmad Rifai; Dwi Septiani; Fahri Hananto Yasin; Lenny Widiawati; Stefany Caroline (Publikasi Indonesia, 2023)
The study aims to highlight the role of accountants in supporting and facilitating the implementation of the Net Zero Emission Programme in Indonesia with a focus on emission measurement and reporting, sustainable financial management, related audits and verification, as well as its impact on environmental sustainability and the achievement of climate change targets. The research is based on a qualitative approach of literature review using data in the form of annual reports and sustainability reports from mining companies in 2022 as well as from various related research journals. The results of this study show that accountants have a key role to play in helping companies and organizations achieve zero emission targets while ensuring compliance with relevant regulations. They can also help in measuring the financial impact of sustainability initiatives and make transparent reports to stakeholders.